(untitled) (Journal of Contemporary Educational Policies and Practices, 2020)
Can Tho University, as a key university in the Mekong Delta region, has strived to exploit E-learning in order to create opportunities and advances to meet learning demands of students inside and outside the region. The paper, based on the university’s E-learning model, analyzes and assesses the reality and proposes some policies to develop this form of training to become one of the common practices of training in the coming time, creating more opportunities for people and communities to participate in a learning society, following the inevitable future trend.